2021
DOI: 10.3389/fimmu.2021.682492
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a Target for Therapeutic Cancer Vaccines and Considerations for Optimizing Their Clinical Potential

Abstract: Telomerase-based therapeutic cancer vaccines (TCVs) have been under clinical investigation for the past two decades. Despite past failures, TCVs have gained renewed enthusiasm for their potential to improve the efficacy of checkpoint inhibition. Telomerase stands as an attractive target for TCVs due to its almost universal presence in cancer and its essential function promoting tumor growth. Herein, we review tumor telomerase biology that may affect the efficacy of therapeutic vaccination and provide insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 147 publications
(174 reference statements)
0
17
0
Order By: Relevance
“…TCVs designed to cover the active site of hTERT are potentially broadly applicable and may serve as an 'offthe-shelf' approach to treat cancer. 18 Theoretically, there should be limited opportunities for resistance mutations to develop, as molecular alterations in the hTERT T cell epitopes would likely negatively affect telomerase activity leading to hampered tumor growth. Characterization of IRs induced by first-generation hTERT vaccines led to the identification of a now clinically validated immunogenic region derived from the active site of hTERT.…”
Section: What This Study Addsmentioning
confidence: 99%
“…TCVs designed to cover the active site of hTERT are potentially broadly applicable and may serve as an 'offthe-shelf' approach to treat cancer. 18 Theoretically, there should be limited opportunities for resistance mutations to develop, as molecular alterations in the hTERT T cell epitopes would likely negatively affect telomerase activity leading to hampered tumor growth. Characterization of IRs induced by first-generation hTERT vaccines led to the identification of a now clinically validated immunogenic region derived from the active site of hTERT.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Therapeutic cancer vaccines aiming to mount anti-hTERT immune responses have been evaluated with several platforms, including peptide, mRNA, and DNA-based approaches [ 28 ]. UV1 is a multipeptide therapeutic vaccine that has demonstrated HLA-independent induction of vaccine-specific T cell responses in patients treated across three completed phase I/IIa clinical trials [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…High tumor telomerase activity is a well-established negative prognostic factor across multiple cancer indications [ 20 24 ], whereas anti-telomerase CD4 T cell immune responses are emerging as independent positive prognostic factors validated in several malignancies [ 25 27 ]. Based on these characteristics, hTERT is considered a promising TAA for therapeutic vaccination [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activating and stimulating the immune system against specific antigens to elicit an anti-tumor immune response using a vaccine is the great purpose of immunization against cancer. Numerous studies showed that using different types of antigens associated with melanoma-related tumors, has yielded excellent results for vaccination (Boël et al 1995 ; Ruault et al 2002 , 2003 ; Weber et al 2011 ; Al-Khadairi and Decock 2019 ; Safavi et al 2019 ; Ellingsen et al 2021 ; Ouyang et al 2021 ; Richard et al 2021 ). We used BLCAP, PRAM, and BAGE4 antigens as key factors in our construct.…”
Section: Discussionmentioning
confidence: 99%